2020
DOI: 10.1128/mbio.03284-19
|View full text |Cite
|
Sign up to set email alerts
|

Plasmids Shaped the Recent Emergence of the Major Nosocomial Pathogen Enterococcus faecium

Abstract: Enterococcus faecium is a gut commensal of humans and animals but is also listed on the WHO global priority list of multidrug-resistant pathogens. Many of its antibiotic resistance traits reside on plasmids and have the potential to be disseminated by horizontal gene transfer. Here, we present the first comprehensive population-wide analysis of the pan-plasmidome of a clinically important bacterium, by whole-genome sequence analysis of 1,644 isolates from hospital, commensal, and animal sources of E. faecium. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
143
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 116 publications
(158 citation statements)
references
References 54 publications
11
143
4
Order By: Relevance
“…Abricate (https://github.com/tseemann/abricate, version 0.8) was used to identify presence of the 18 E. faecium E745 genes that had the largest role in survival in PBS, as determined by Tn-seq, against the draft assemblies from 1,644 E. faecium genomes that represent the global diversity of the species E. faecium [58]. We considered a minimum identity and coverage of 95% and 80%, respectively, to consider a gene as present in a particular draft assembly.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Abricate (https://github.com/tseemann/abricate, version 0.8) was used to identify presence of the 18 E. faecium E745 genes that had the largest role in survival in PBS, as determined by Tn-seq, against the draft assemblies from 1,644 E. faecium genomes that represent the global diversity of the species E. faecium [58]. We considered a minimum identity and coverage of 95% and 80%, respectively, to consider a gene as present in a particular draft assembly.…”
Section: Methodsmentioning
confidence: 99%
“…We considered a minimum identity and coverage of 95% and 80%, respectively, to consider a gene as present in a particular draft assembly. To visualize the presence and absence of these genes in the context of the phylogeny of E. faecium , we used the neighbour-joining tree described in [58], based on a RAxML tree-based of 955 E. faecium core genes, and used the R package ggtree (version 1.14.6) to plot the presence of the different E745 genes.…”
Section: Methodsmentioning
confidence: 99%
“…Recombination events and estimation of sequence clusters using BratNextGen and hierBAPS were performed as previously described (21). PopPUNK (version 2.0.1) was run specifying the flag '--easy-run' with a minimum k-mer size of 13 (flag --min-k) and creating the files required to generate a microreact project (flag --microreact) (27).…”
Section: Population Structure Of Vrefm Isolatesmentioning
confidence: 99%
“…Previous whole genome sequencing (WGS) studies identified a split in the E. faecium population into two lineages, including a hospital-associated clade (clade A) and a communityrelated clade (clade B) (5,6). Later, clade A was subdivided into clade A1 representing the majority of hospital associated isolates and clade A2 for animal-related isolates (7), although two studies which included a larger collection of animal-related isolates suggested that these isolates clustered in polyphyletic groups and not in a distinct clade A (8,9). In a recent study also including 55 isolates from Latin America, phylogenomics suggests that the animal isolates represent multiple lineages that diverged prior to the emergence of the clinical subclades in clade A (10).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, we determined the plasmid content (plasmidome) of 1,644 E. faecium isolates from different sources, countries and years using short-and long-read whole genome sequencing technologies in combination with machine-learning classifiers (9,11). This analysis revealed that the hospital-associated isolates carried a larger number of plasmid sequences compared to isolates from other sources and different configurations of plasmidome populations in the hospital environment.…”
Section: Introductionmentioning
confidence: 99%